Formulation and Evaluation of Natural Spray Deodorant Based on Milk Whey Kefir and Lime Extract - Windayani, Neneng; Jualiah, Siti; Hidayat, Robby Nur; Azizah, Ainun; Sitoresmi, Wibi Apsari; Zulfikor, Ahmad; Sa’diah, Fitri Yati (Faculty of Animal Science Universitas Brawijaya, 2025)
Body odor can reduce self-confidence and social interaction. Commercial deodorants often contain aluminum compounds and synthetic chemicals that may cause health problems. This study aims to formulate and evaluate an environmentally friendly deodorant using milk whey kefir and lime extract. Three formulations (F1, F2, F3) were developed using different ratios of alum and whiting. Organoleptic, hedonic, and Malodor Counteraction (MOC) tests were conducted. F1 showed the best stability and sensory preference among 16 panelists. Based on the hedonic test results, Formulation F1 received the highest score at 43.75%, establishing it as the most preferred formula among panelists. This strong preference is primarily attributed to its highest concentration of lemon essential oil (0.30 mL). Certainly, lime extract also significantly influences the aroma and texture of the resulting formulation. This generous inclusion of lime extract and lemon essential oil not only imparts a distinctly fragrant aroma but also creates a unique and characteristic scent profile when combined with milk whey kefir. This particular aromatic blend is highly effective at masking unpleasant body odors, making the formulation exceptionally suitable for its intended purpose. Consequently, its appealing fragrance significantly contributed to panelists selecting F1 as the most fitting natural spray deodorant formula. The pH stability over 45 days indicated consistency in F1 and F2, while F3 showed a significant drop. These findings suggest that milk whey kefir and lime extract can be effectively utilized in deodorant formulations.